Digital Transformation of MARA University of Technology (UiTM) to the University of the future and enhancement of business model - Mahazan, Nurhasyifha; Abdullah, Nursyafawati; Mohd Radzi, Amal Nadhira; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
This paper explains the digital transformation of MARA University of Technology (UiTM) to become the university of the future. As countries worldwide have become increasingly interconnected due to globalization, universities have likewise undergone significant changes. To achieve and maintain academic and research excellence in today’s fast-paced knowledge economy, it is critical for the international universities to transcend traditional education. Several Asian universities have acquired top academic rankings and achieved international recognition in parity with many western iconic counterparts. These rankings have galvanized the world of higher education, resulting in a virtuous circle impact on universities’ drive for academic and research excellence. Since the emergence of global ranking, universities have been compared on a national and international basis and this has affected the way they operate. The rankings-used as the tool to maintain and build the institutional position and reputation-have also resulted in an increasing trend of policy makers utilizing the ranking results to decide on resource a location or structure of higher education system counterparts.